2020
DOI: 10.1111/1440-1703.12173
|View full text |Cite
|
Sign up to set email alerts
|

Mismatched spatial scales can limit the utility of citizen science data for estimating wildlife‐habitat relationships

Abstract: While most carnivore populations are declining worldwide, some species are successfully living in human-modified landscapes. For example, coyotes (Canis latrans) have expanded their range across North America and into many urban areas making it important to understand factors influencing broad-scale patterns of occurrence. We used citizen science data in the form of coyote observations by archery deer hunters from throughout the state of Illinois to evaluate factors affecting coyote detection and occupancy. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The highest traffic volumes were located towards the edge of the study area, coinciding with sites of high suitability due to other characteristics, such as high garden cover and lower urban pressure. As traffic volume data were only available at the local authority level, they may be too broad to detect hedgehogs’ habitat relationships, a problem that has previously been highlighted (Bauder et al 2021). More detailed research on fine‐scale spatial relationships between hedgehogs and traffic within otherwise suitable suburban habitat is therefore important.…”
Section: Discussionmentioning
confidence: 99%
“…The highest traffic volumes were located towards the edge of the study area, coinciding with sites of high suitability due to other characteristics, such as high garden cover and lower urban pressure. As traffic volume data were only available at the local authority level, they may be too broad to detect hedgehogs’ habitat relationships, a problem that has previously been highlighted (Bauder et al 2021). More detailed research on fine‐scale spatial relationships between hedgehogs and traffic within otherwise suitable suburban habitat is therefore important.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand the limitations of citizen science and ensure any assumptions are met before employing this method (e.g. Bauder et al, 2021;Jäckel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian analysis of clustering using STRUCTURE (Pritchard et al, 2000) identified three as the most likely value of K. However, the sampled individuals did not group into distinct subpopulations; instead, all individuals were inferred to share some degree of admixture from all three genetic clusters. This suggests that our samples Therefore, our analyses suggest spatial separation may be the main factor that limits gene flow and dispersal of the Persian squirrel in this area (Bauder, Cervantes, et al, 2021). In many mammal species, IBR models that account for the heterogeneity in species' distributions and migration rates better explain the genetic structure of populations in comparison to IBD models (Coulon et al, 2006 Nonetheless, there are several other mammals, including some with high dispersal ability like Goitered gazelle, Gazella subgutturosa, or white-tailed deer, Odocoileus virginianus, for which distributions are better explained by geographical distance than landscape matrix (Bauder, Cervantes, et al, 2021;Khosravi et al, 2018;Mullins et al, 2014).…”
Section: Discussionmentioning
confidence: 77%